Susceptibility of eight species members in the Anopheles hyrcanus group to nocturnally subperiodic Brugia malayi - Saeung A. (2014)
Background: Filariasis, caused by Brugia malayi, is a public health problem in Thailand. Currently, at least two locations in southern Thailand are reported to be active endemic areas. Two and four Mansonia species are primary and secondary vectors, respectively, of the nocturnally subperiodic race, whereas, Coquillettidia crassipes is a vector of the diurnally subperiodic race. Although several Anopheles species have been incriminated extensively as natural and/or suspected vectors of B. malayi, little is known about vector competence between indigenous Anopheles and this filaria in Thailand. Thus, the susceptibility levels of eight species members in the Thai An. hyrcanus group to nocturnally subperiodic B. malayi are presented herein, and the two main refractory factors that affect them in different degrees of susceptibility have been elucidated. Methods. Aedes togoi (a control vector), An. argyropus, An. crawfordi, An. nigerrimus, An. nitidus, An. paraliae, An. peditaeniatus, An. pursati and An. sinensis were allowed to feed artificially on blood containing B. malayi microfilariae, and dissected 14 days after feeding. To determine factors that take effect at different susceptibility levels, stain-smeared blood meals were taken from the midguts of Ae. togoi, An. peditaeniatus, An. crawfordi, An. paraliae, An. sinensis and An. nitidus immediately after feeding, and their dissected-thoraxes 4 days post blood-feedings were examined consecutively for microfilariae and L§ssub§1§esub§ larvae. Results: The susceptibility rates of Ae. togoi, An. peditaeniatus, An. crawfordi, An. nigerrimus, An. argyropus, An. pursati, An. sinensis, An. paraliae and An. nitidus to B. malayi were 70-95%, 70-100%, 80-85%, 50-65%, 60%, 60%, 10%, 5%, and 0%, respectively. These susceptibility rates related clearly to the degrees of normal larval development in thoracic muscles, i.e., Ae. togoi, An. peditaeniatus, An. crawfordi, An. paraliae, An. sinensis and An. nitidus yielded normal L§ssub§1§esub§ larvae of 93.15%, 96.34%, 97.33%, 23.60%, 15.38% and 0%, respectively. Conclusions: An. peditaeniatus, An. crawfordi, An. nigerrimus, An. argyropus and An. pursati were high potential vectors. An. paraliae and An. sinensis were low potential vectors, while An. nitidus was a refractory vector. Two refractory mechanisms; direct toxicity and/or melanotic encapsulation against filarial larval were involved in the refractoriness of development in the thoracic muscles of the mosquito. © 2013 Saeung et al.; licensee BioMed Central Ltd.